State-Owned Enterprises’ Role in the Implementation of the State Innovation Policy - N. D. Frolova; N. V. Shashkova (Ekonomika Nauki)
This paper examines how state-owned enterprises are involved in the implementation of the state innovation policy. The research method is a comparative analysis of statistical data on innovation activity of Russian organizations of private ownership and organizations in which the state acts as one of the owners. The research period is 2019–2023. The results of the study show that state-owned enterprises are characterized by higher indicators of innovative activity of organizations: they innovate more often, the average expenses for innovative activity exceed the same indicator of private organizations several times (4.3 times by the end of 2023), the share of innovative goods, works and services in the total volume of delivered goods and rendered works and services of state-owned enterprises. The high potential of state-owned enterprises in the creation and coordination of innovation systems is noted. The factors that reduce the efficiency of state joint-stock companies as subjects of implementation of the state innovation policy are noted: “Conflict of state goals”, which leads to withdrawal of resources and restraint of expenditures on R&D and innovation, as well as information closure, which contributes to the increase of a number of risks.